The Influence of Al-Ghazali's Sufistic Thought on Pesantren Education Practices in Indonesia - Mahdany, Diny; Mahmud; Muhammad Toriqularif; Hamsinah; Zuhriah (At-Taqaddum, 2025)
Pesantren education in Indonesia faces challenges in integrating the development of spiritual, moral, and academic competence of santri in a balanced manner. Al-Ghazzali's Sufistic thought is considered relevant to strengthen pesantren education practices because it emphasises purification of the soul (tazkiyatun nafs), moral development (tarbiyatul akhlaq), and systematic dhikr practices. This study aims to analyse the influence of al-Ghazzali's Sufistic principles on pesantren education practices in Indonesia. The research used a qualitative approach with a descriptive-analytic type to obtain an in-depth understanding of the implementation of Sufistic values in the context of pesantren education. Data were collected through in-depth interviews with kyai, ustaz, and santri; participatory observation of learning and worship activities; and documentation of curriculum and teaching records. Data analysis was conducted through reduction, presentation, and triangulation to ensure the validity and consistency of the findings. The results show that the application of the tazkiyatun nafs principle encourages santri to conduct self-reflection, routine dhikr, and spiritual evaluation so as to increase self-awareness, discipline, and emotional control. The principle of tarbiyatul akhlaq through moral mentoring and social activities strengthens the character, empathy, and social responsibility of santri. The integration of al-Ghazzali's Sufistic values in the curriculum and daily activities creates a balance between intellectual and spiritual aspects, forming students who are spiritually mature, noble, and able to interact harmoniously in society. In conclusion, al-Ghazzali's Sufistic thought plays a significant role in improving the quality of pesantren education holistically. Future research is recommended to compare pesantren that apply Sufistic principles with those that do not, as well as examining the application of Sufistic.